2016
DOI: 10.4172/2157-7110.1000609
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Trifoliate Yam (Dioscorea dumetorum) in Noodles Production

Abstract: Trifoliate yam (Dioscorea dumetorum) is a high yielding but under exploited yam species. Potential of its flour in noodle production was investigated in this study. Trifoliate yam flour was produced and substituted for wheat flour at 20 -70% levels. Noodles were produced from the composite flour and evaluated for their proximate composition, functional properties, colour and cooking properties, using standard methods. Sensory attributes of the noodle were also determined using panelists. Data were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Comparable results were reported from noodles produced from wheat/orange fleshed sweet potato/African bean yam flour noodles which ranged from 11.67-13.04% [17]. Protein content of the noodles in the present study was higher than 5.88-7.79% for trifoliate yam-wheat noodles [5], 2.63-4.47% for yellow noodles substituted with mangosteen pericarp powder [30]. This result therefore indicates that noodles of improved protein could be produced from substitution of wheat flour with cowpea flour, acha flour and MLP.…”
Section: Proximate Composition Of Noodles Produced From Wheat Flour supporting
confidence: 61%
See 1 more Smart Citation
“…Comparable results were reported from noodles produced from wheat/orange fleshed sweet potato/African bean yam flour noodles which ranged from 11.67-13.04% [17]. Protein content of the noodles in the present study was higher than 5.88-7.79% for trifoliate yam-wheat noodles [5], 2.63-4.47% for yellow noodles substituted with mangosteen pericarp powder [30]. This result therefore indicates that noodles of improved protein could be produced from substitution of wheat flour with cowpea flour, acha flour and MLP.…”
Section: Proximate Composition Of Noodles Produced From Wheat Flour supporting
confidence: 61%
“…Seasonings from the commercial indomie noodles wew added to taste and cooked until the water almost dried up. The cooked noodles were coded and served the panelists for sensory analysis.The statistical analysis of data collected was used to select five(5) generally accepted samples (100% Triticum durum; 75% Triticum durum and 25% Vigna unguiculata; 50% Digitaria exilis and 50% Vigna unguiculata; 50% Triticum durum, 23% Digitaria exilis, 25% Vigna unguiculata and 2% Moringa oleifera; and 75% Triticum durum and 25% Digitaria exilis) based on significantly highest means in the different parameters used.…”
mentioning
confidence: 99%
“…The low moisture in the sample could be attributed to the baking process which has the capacity to extract almost all available free moisture. The results of moisture content were within the safe moisture level (≤10%) for long term storage of flour (Akinoso et al, 2016) Solomon and Judith (2020) for melon-groundnut kuli-kuli. The values were higher than (7%-8%) minimum recommended for prevention of PEM (Protein-energy malnutrition) by FAO/WHO/UNU (1985).…”
Section: Pea Floursupporting
confidence: 59%
“…The value obtained indicated that the value increased with increase in pigeon pea incorporation. The ash content in pigeon pea is higher than that of groundnut and could be responsible for the increase in the ash obtained (Akinoso et al, 2016). It then follows that incorporation of pigeon pea in the process of snack making could enhance the mineral intake of many people, as ash is indicative of the amount of minerals contained in any food sample.…”
Section: Pea Flourmentioning
confidence: 97%
“…Food mineral compositions such as calcium, magnesium, potassium, sodium, manganese, iron, copper, zinc are of great importance for scientists and practitioners working in the fields of nutrition and public health (Chinedu et al, 2017 andWalter et al, 2016). Some authors (Amusa et al, 2012;Rahman et al, 2016;Adebowale and Leal, 2003;Afoakwa et al, 2001;Ide et al, 2019, Ugwunyi-Nnad et al, 2019Kiin-Kabari and Giami, 2015;Amandikwa et al, 2015;Asif-Ul et al, 2014;Olualana et al, 2011;Adeleke and Odedeji, 2010;Supaluk et al, 2017;Anthony et al, 2014;Toyin, 2001;Akpata and Miachi,2001;Nwosu, 2011;Iwe et al, 2016;Owuamana et al, 2016) reported on functional properties and mineral compositions of different food products. This research focused on the effects of processing methods on functional properties and mineral compositions of cashew varieties kernel flour which will aid the provision of required human nutrients and also enhance the development of new food products.…”
Section: Introductionmentioning
confidence: 99%